Towards transdisciplinarity in technology and resource management research: A project in Ethiopia - Jabbar, M.A.; Mohamed-Saleem, M.A.; Li-Pun, H. (2001)
The paper first discusses the need for moving from disciplinary to transdisciplinary research in addressing problems of human development and environmental management. Then the experience of a research project in highland Ethiopia is described. This started with disciplinary research and component technologies to address problems of poverty, malnutrition, low agricultural productivity and resource degradation, and gradually moved towards integrated resource management and a transdisciplinary approach. Although a systems approach was adopted to diagnose problems, discipline-based component technology research was initially a dominant characteristic of the project. Individual technologies were designed and tested on farm with farmer participation - often separately, and their impacts were assessed mostly in bio-economic terms, eg for yield and income. Gradually the need for simultaneously assessing the economic, social and environmental effects of several technology interventions at plot, household and watershed/community levels was recognized. The research methods have been modified accordingly to adopt an integrated and holistic approach incorporating biophysical, economic and social dimensions of the ecosystem. An agroecosystem health approach to ecosystem analysis is currently being used as an integrative analytical framework. This evolution has also meant a gradual shift from a disciplinary to a multidisciplinary, and finally to a transdisciplinary approach to research.